STUDI LITERATUR: PENGARUH MOTIVASI, KOMUNIKASI DAN KEPEMIMPINAN GUNA MENINGKATKAN SEMANGAT KERJA PEGAWAI - Dendy Eta Mirlana (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
Motivation, Communication, Leadership, and Morale. Previous research is very important in a research or article. Previous research serves to strengthen the theory and phenomena of the relationship or influence between variables. The aims of this research article are: 1). To determine the effect of work motivation on increasing employee morale, 2). To determine the effect of work communication on increasing employee morale, 3). To determine the influence of leadership in increasing employee morale in an agency or organization. This type of research is library research. The method used is a literature study. The results of the literature study in this study indicate that employee morale is influenced by motivation, communication and leadership.